Insights into the epidemiology of community-associated methicillin-resistant Staphylococcus aureus in special populations and at the community-healthcare interface - Romero, Letícia Calixto [UNESP]; de Souza da Cunha, Maria de Lourdes Ribeiro [UNESP] (Elsevier, 2021)
The current epidemic proportions of infections caused by Staphylococcus aureus strains and especially by methicillin-resistant S. aureus (MRSA) are one of today's many threats to global public health, particularly in underdeveloped countries where significant gaps on the subject exist. The rapid spread and diversification of pandemic clones that exhibit remarkably increasing virulence and antimicrobial resistance pose a risk to the effective prevention and treatment of a wide range of infections. Undoubtedly, the remarkable versatility involving the pathogenesis and resistance of these bacteria is perpetuated through geographic and temporal factors inherent to clonal evolution and is reflected in the dramatic epidemiological changes of MRSA which, after decades prevailing in healthcare settings, have emerged in the community. Denominated community-associated [CA]-MRSA, these strains are particularly prevalent in some population groups, facilitating the spread of successful clones that are potentially capable of triggering severe community-acquired infections. Therefore, a broad approach to local epidemiological aspects in less studied regions, but nonetheless at latent risk of endemic spread that may reach global proportions, is necessary. In Brazil, despite limited molecular epidemiology data, CA-MRSA strains predominantly characterized as SCCmec IV, often classified as CC30-ST30, CC5-ST5 and CC8-ST8, seem to be spreading across different population groups in different regions of the country. Another important fact addressed in this review is the identification of the ST398-MRSA-IV/V clone and methicillin-susceptible S. aureus (MSSA) in healthy individuals from the community. Although susceptible to methicillin, the ST398 clone is associated with severe infections in humans and animals, denominated livestock-associated MRSA. It is therefore important to encourage assertive actions by all government sectors and by society, with a reassessment of current public health measures in light of the new perspectives arising from the scientific and epidemiological data on MRSA.
Keywords: CA-MRSA; LA-MRSA; Molecular typing; MRSA evolution; Nasal carriage; SCCmec